IMPLEMENTASI EVEKTIVITAS TEORI BELAJAR KONTRUKTIVISME PADA METODE PENEMUAN MENINGKATKAN HASIL BELAJAR SISWA SMP NEGERI 1 STABAT - Hendrik, Hendrik; Mardiana Panggabean, Ellis (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2021)
The purpose of this research is to find out whether the application of constructivism learning theory to the discovery method can increase the effectiveness of student learning. 2. to find out how the application of constructivism learning theory to the discovery method can increase the effectiveness of student learning. This research was carried out by giving the discovery method learning treatment to the subjects of Stabat 1 Public Middle School students. From the results of data analysis, it was found that students' mastery of material was 76.91% in the medium category, classical learning mastery was 87.3%, achievement of specific learning objectives as a whole was 80%. Based on the results of this study, it can be concluded that learning mathematics using the discovery method at Stabat 1 Public Middle School is effective. So this method can be an alternative method of learning mathematics.